Deep functional measurements of Fragile X syndrome human neurons reveal multiparametric electrophysiological disease phenotype - James J. Fink; Nathaniel Delaney-Busch; Ryan Dawes; Evanthia Nanou; Christopher Folts; Karthiayani Harikrishnan; Chris Hempel; Hansini Upadhyay; Trinh Nguyen; Himali Shroff; David Stoppel; Steven J. Ryan; et al. (Communications Biology)
Abstract Fragile X syndrome (FXS) is a neurodevelopmental disorder caused by hypermethylation of expanded CGG repeats (>200) in the FMR1 gene leading to gene silencing and loss of Fragile X Messenger Ribonucleoprotein (FMRP) expression. FMRP plays important roles in neuronal function, and loss of FMRP in mouse and human FXS cell models leads to aberrant synaptic signaling and hyperexcitability. Multiple drug candidates have advanced into clinical trials for FXS, but no efficacious treatment has been identified to date, possibly as a consequence of poor translation from pre-clinical animal models to human. Here, we use a high resolution all-optical electrophysiology platform applied to multiple FXS patient-derived and CRISPR/Cas9-generated isogenic neuronal cell lines to develop a multi-parametric FXS disease phenotype. This neurophysiological phenotype was optimized and validated into a high throughput assay based on the amount of FMRP re-expression and the number of healthy neurons in a mosaic network necessary for functional rescue. The resulting highly sensitive and multiparameter functional assay can now be applied as a discovery platform to explore new therapeutic approaches for the treatment of FXS.